The Concept of Achievement of Insan Kamil According to Sheikh Muhammad Nafis Al- Banjari (Conference Series, 2022)
Humans frequently engage in the act of praying. Those who hold religious beliefs and faith are likely to pray on a daily basis. Typically, when people pray, they make requests or express their thoughts to their Creator. Prayer is commonly perceived as a way to communicate with God. During prayer, individuals speak and interact with God, anticipating a response. Consequently, prayer is not an unfamiliar or unusual practice for humans since it involves speaking directly to God. This qualitative research study aims to explore the role of prayer in the spiritual lives of Christian believers using a Bible exegetical approach, in particular the Lord’s Prayer. The research utilizes the extensive knowledge and background of biblical passages in Matthew 6:5-13 that are connected to prayer with the objective of understanding the beliefs, practices, and experiences of Christian believers. Findings reveal that prayer plays a significant role in the spiritual lives of Christian believers, providing a means of communication with God, fostering a sense of intimacy and relationship with God, and serving as a source of comfort, guidance, and empowerment.